WHY A RN FIRST ASSISTANT? A Look at the Benefits... - Groetzsch, Grace (Operating Room Nurses Association of Canada Journal, 2003)
Can a Registered Nurse First Assistant (RNFA) work effectively as a first assistant to the surgeon and the patient? This article will examine the RNFA role and the benefits it provides to the healthcare system.